2015
DOI: 10.1016/j.aidm.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy and safety of EUS‐FNA for diagnosis of mediastinal and abdominal solid tumors – A single center experience

Abstract: Background: Many tumors are small and located around the gastrointestinal (GI) tract, and they are difficult to obtain tissue from for pathological diagnosis by the guidance of conventional methods (sonography or computed tomography. The aim of this study was to analyze the efficacy and benefit of endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) in the clinical diagnosis of solid tumors in the mediastinum and abdomen. Patients and methods: Data from 233 patients with solid tumors on or around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The accuracy for pancreatic lesions and perigastric lymph nodes was significantly smaller (<80%) [ 38 ]. Analyzing data from 91 patients with pancreatic tumors, Sheng-ShunYang et al showed similar results for EUS-FNA diagnostic accuracy (79.2%) [ 39 ]. As in our case, EUS-FNA remains a valuable diagnostic tool, especially when surgery is not feasible; however, it may yield discrepant results, mostly in settings with a limited amount of diagnostic material for an accurate tumor grading.…”
Section: Discussionmentioning
confidence: 93%
“…The accuracy for pancreatic lesions and perigastric lymph nodes was significantly smaller (<80%) [ 38 ]. Analyzing data from 91 patients with pancreatic tumors, Sheng-ShunYang et al showed similar results for EUS-FNA diagnostic accuracy (79.2%) [ 39 ]. As in our case, EUS-FNA remains a valuable diagnostic tool, especially when surgery is not feasible; however, it may yield discrepant results, mostly in settings with a limited amount of diagnostic material for an accurate tumor grading.…”
Section: Discussionmentioning
confidence: 93%